ENHANCING CRITICAL THINKING SKILLS THROUGH STEM PROBLEM-BASED CONTEXTUAL LEARNING: AN INTEGRATED E-MODULE EDUCATION WEBSITE WITH VIRTUAL EXPERIMENTS - Pertiwi, Nanda Putri; Saputro, Sulistyo; Yamtinah, Sri; Kamari, Azlan (Journal of Baltic science education, 2024)
One of the skills needed in the 21st century is critical thinking skills that need to be developed for secondary school students. Currently, upper-secondary students' critical thinking skills are still low. To overcome the problem, website-based E-module learning media was developed using a STEM approach with a Problem-Based Contextual Learning model with virtual experiments using PhET. The aim of developing this website-based E-Module media is to improve students' thinking skills on thermochemistry learning materials. The development model is 4-D. Data collection in this study was gained from three schools representing schools in the high, medium, and low categories in Surakarta, Indonesia. In this research,216 students were involved as the subjects at the development module implementation stage. The results of expert validation of the material, language, and media modules are suitable for use with a score of 90.03% categorized as very good. In the feasibility test, the score was 87.98% categorized as very good. The score for critical thinking skills was 79.18% in the critical category. N-Gain score was 0.70 categorized as high criteria. The result of the independent sample t-test sig 0.023, Critical thinking skills were conducted using E-Module. The results are higher than conventional media and effective in improving students’ critical thinking skills.